Perjanjian Indonesia Rusia Kerjasama Bilateral Ekonomi dan Teknik - Zailani Lubis; Natasya , Natasya; Tamaulina Br.Sembiring (PT. ALHAFI BERKAH INDONESIA, 2024)
This article discusses the cooperation agreement between Indonesia and the Russian Federation regarding Economic and Technical Cooperation on March 12, 1999. The research article aims to explore the process of establishing this cooperation, the background of the cooperation. The relationship between Indonesia and Russia began not just as a business relationship between two countries but as a close friendship akin to two brothers that has lasted for 77 years since 1945. On January 25, 1950, the Soviet Foreign Minister A. Vyshinsky formally recognized Indonesia's independence and sovereignty in a written communication to Indonesia's Prime Minister/Foreign Minister M. Hatta, expressing the Soviet Union's desire to establish diplomatic relations. This article was written as an assignment for International Law studies to achieve academic credit.